Kondisi Ekonomi Masyarakat Petani Nilam - Ahmad, Amirzah; Kasmiati, Sitti; Nursalam, La Ode (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2026)
Patchouli (Pogostemon cablin Benth.) is one of the main agricultural commodities cultivated by the community in Mataupe Village. However, the economic condition of patchouli farmers varies considerably, indicating the need for a more in-depth study of their socioeconomic aspects. This research aims to describe the economic condition of patchouli farmers in Mataupe Village, Andoolo Barat Subdistrict, South Konawe Regency. The study employed a descriptive qualitative method, with data collected through observation, questionnaires, and documentation. The results showed that the size of farmland managed by farmers varies: 15 farmers (36%) cultivate less than 0.5 hectares, 15 farmers (36%) cultivate 0.5 hectares, 10 farmers (24%) manage between 0.5–2 hectares, and only 2 farmers (4%) own 2 hectares of land. In terms of income, based on BPS (Central Bureau of Statistics) classification, 33 farmers (78.6%) fall into the very high-income category, 6 farmers (14.3%) into the high-income category, and 3 farmers (7.1%) into the moderate-income category. Regarding household expenditure, 2 farmers (5%) have very high expenditures, 11 farmers (26%) high, 18 farmers (43%) moderate, and 11 farmers (26%) low. These findings illustrate the diverse economic capacities among patchouli farmers in Mataupe Village, which are strongly influenced by differences in land size, production scale, and household spending priorities.